Representasi Nilai Kekeluargaan dalam Film Everything Everywhere All At Once - Siti Shafa Divayani; Doddy Iskandar (Bandung Conference Series: Public Relations, 2023)
Abstract. The film tells of a Chinese woman named Evelyn wang who lived in America with her husband, son, and father, running a laundry business but on the verge of bankruptcy. Then he had to care for his business taxes, but what followed changed Evelyn's life completely. The purpose of this study was to understand the familiar values of Everything Everywhere All At Once. The research method used in this study is qualitative research methods using a semiotics analysis approach John Fiske’s semiotics theory that presents the concept of television encoding into three levels reality, representative level, and ideology level. The results of this study indicate adopted values contained in everything everywhere all at once including aspects of behavior, costume, appearance, speech, attitude, shooting techniques, lighting techniques, and matriarch. The importance of a mother's role in parenting and educate, being both a protector and a guardian of the family. On the other hand, even mothers have a role to take care of. Abstrak. Film ini mengisahkan seorang perempuan asal China bernama Evelyn Wang yang tinggal di Amerika bersama suami, anak dan ayahnya, menjalankan sebuah bisnis binatu namun berada diambang kebangkrutan. Ia pun harus mengurusi pajak bisnisnya, namun apa yang terjadi setelahnya mengubah hidup Evelyn sepenuhnya. Tujuan dari penelitian ini adalah untuk mengetahui nilai-nilai kekeluargaan yang ada pada film Everything Everywhere All At Once. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian kualitatif dengan menggunakan teori semiotika John Fiske yang mengemukakan konsep pengkodean televisi yang terbagi menjadi tiga level yaitu level realitas, level representasi, dan level ideologi. Hasil dari penelitian ini menunjukkan nilai-nilai kekeluargaan yang terkandung dalam film Everything Everywhere All At Once mencakup aspek perilaku, kostum, penampilan, gaya bicara, sikap, teknik pengambilan gambar, teknik pencahayaan, dan matriarki. Pentingnya peran ibu dalam mengasuh dan mendidik anak, menjadi pelindung sekaligus penjaga keluarga. Di sisi lain, ibu pun memiliki peran dalam mengurusi alur keuangan yang ada dalam rumah tangga dan memenuhi segala kebutuhan keluarga.